THE ANALYSIS OF SUBTITLING STRATEGIES IN MOON KNIGHT EPISODE 6 TV SERIES - Richatuzzahra, Richatuzzahra; Djohan, Rita Sutjiati (Universitas Gunadarma, 2024)
The objective of this research is to identify the subtitling strategies used in the Moon Knight TV series episode 6 and to find out the most commonly used subtitling strategy in the Moon Knight TV series episode 6. This researcher used the qualitative-descriptive method. Based on the data findings, the researcher found 10 out of 10 strategies, namely transfer, imitation, transcription, expansion, paraphrase, dislocation, condensation, deletion, decimation, and resignation. There are 139 data of transfer strategy, 72 data of imitation strategy, condensation strategy with the total 41 data, dislocation strategy with the total 33 data, paraphrase strategy with the total 29 data, expansion strategy with the total 12 data, transcription strategy with the total 9 data, decimation strategy with the total 5 data, deletion strategy with the total 3 data, and the last resignation strategy with the total of 1 data. The most used strategy in the Moon Knight TV series episode 6 found by the researcher is the transfer strategy, with a total of 139. The least used strategy is the resignation strategy, with a total of the data 1. In short, utterance from the source language is can be translated accurately. In another occasion, translator used resignation strategy because translator doesn’t have any solution to the translation process which causes a loss of meaning, beside that in audio-visual there are no part can provide an explanation of the meaning of the source language. And translating the subtitle or text just makes an ambiguous or incorrect translation in the TV series.